the Evolution of Pink: Morphological and Genetic Variation Among Three Lithophragma (Saxifragaceae) Species (2006)
Prior molecular work using ITS and chloroplast sequence data revealed that the endemic Lithophragma trifoliatum and the broad-ranging L. parviflorum form a tight clade with a third species, L. affine. We used AFLPs to assess the fine scale relationship of these three species from populations where their distributions overlap in northern California. Our results revealed two groups of L. trifoliatum, one nested within a group of L. affine and L. parviflorum and the other grouped with other populations of L. parviflorum, contrary to predictions based on plant morphology alone. The morphological pattern was not supported by the molecular data, suggesting that pink flowers evolved more than once, concurrently with other floral traits such as size and nectary length. It is also possible that this pattern is due to recent evolution or gene flow between the two color morphs. The possible ecological importance of these differences in floral traits (e.g., for pollination) warrants further study, as well as the extent to which these populations are reproductively isolated.